Rom, Italien: Basilica Aemilia und Basilica Iulia am Forum Romanum - Freyberger, Klaus Stefan (e-Forschungsberichte des DAI, 2023)
According to Livius’s tradition (40, 51, 4–5), the original building was officially consecrated by the Censors M. Aemilius Lepidus and M. Fulvius Nobilior in the year 179 BC. After a fire in 14 BC it was fundamentally renovated and embellished with marble during the rule of Emperor Augustus. The Basilica Aemilia worked as a bank and a place for selling luxurious goods made of precious metals. Beyond that the building served as a low-court in which financial tribunals took place.